Sustainability Investigation of the Old Mustansiriya Madrasa in Modern Construction: A Comparative Study - Jabbar, Adil Mahdi; Al-Shammari, Rabee Jameel; Senah, Husam Sachit; Altameemi, Ayam Sh. (Journal of Islamic Architecture, 2025)
This paper explores the sustainable concepts performed in the Old Mustansiriya Madrasa constructed in Baghdad during the Abbasid era in the thirteenth century AD. The principles and main techniques of sustainability used for modern buildings were compared with the design concepts implemented in the Old Madrasa to extract the most significant concepts that could be applied in designing modern school buildings. The findings showed that the Mustansiriya Madrasa was a distinctive example of Islamic architecture, which included sustainable features. It contained sustainability concepts derived from Islamic teachings and the Holy Quran. The design concept depended on a rectangular shape with a central hollow courtyard for improving natural ventilation and lighting. The Madrasa location was chosen on the Tigris River bank, and landscaping inside and near the building provided natural cooling, air circulation, and filtering. Thick brick walls provided thermal mass techniques to benefit solar energy. Skylights in the narrow halls and corridors provided a distinct energy system. Also, its construction depended on materials that did not affect the environment and were highly durable. Therefore, sustainability concepts were applied 792 years ago in Islamic architecture. Nowadays, designers could learn more from those architectures and their construction methods to reduce the negative impact of recent construction strategies on the environment and human life. Sustainability concepts from the past can be adapted to modern designs. It sounds like a modern school design implementation of these principles was successful.